Species distribution and antifungal susceptibility of 358 Trichosporon clinical isolates collected in 24 medical centres. (July 2019) - Francisco, E.C.; de Almeida Junior, J.N.; de Queiroz Telles, F.; Aquino, V.R.; Mendes, A.V.A.; de Andrade Barberino, M.G.M.; de Tarso O. Castro, P.; Guimarães, T.; Hahn, R.C.; Padovan, A.C.B.; Chaves, G.M.; Colombo, A.L.
Abstract: Objectives: To provide species distribution and antifungal susceptibility profiles of 358 Trichosporon clinical isolates collected from 24 tertiary-care hospitals. Methods: Species identification was performed by sequencing the IGS1 region of rDNA. Antifungal susceptibility testing for amphotericin B, fluconazole, voriconazole and posaconazole followed the Clinical and Laboratory Standards Institute reference method. Tentative epidemiologic cutoff values (97.5% ECVs) of antifungals for Trichosporon asahii were also calculated. Results: Isolates were cultured mostly from urine (155/358, 43.3%) and blood (82/358, 23%) samples. Trichosporon asahii was the most common species (273/358, 76.3%), followed by T. inkin (35/358, 9.7%). Isolation of non– T. asahii species increased substantially over the last 11 years [11/77 (14.2%) from 1997 to 2007 vs. 74/281, (26.3%) from 2008 to 2018, p0.03]. Antifungal susceptibility testing showed high amphotericin B minimum inhibitory concentrations against Trichosporon isolates, with higher values for T. faecale. The ECV for amphotericin B and T. asahii was set at 4 μg/mL. Among the triazole derivatives, fluconazole was the least active drug. The ECVs for fluconazole and posaconazole against T. asahii were set at 8 and 0.5 μg/mL, respectively. Voriconazole showed the strongest in vitro activity against the Trichosporon isolates; its ECV for T. asahii was set at 0.25 μg/mL after 48 hours' incubation. Conclusions: Trichosporon species diversity has increased over the years in human samples, and antifungal susceptibility profiles were species specific. Trichosporon asahii antifungal ECVs were proposed, which may be helpful to guide antifungal therapy.